Análise da variabilidade pluvial na Unidade de Gerenciamento de Recursos Hídricos do Paraíba do Sul (UGRHI-2) - Moraes, Mariana de Paula Costa (2014)
The study of variability becomes increasingly important nowadays . Studying the behavior of rainfall before external events is of paramount importance. The region of Vale do Paraíba , it is important to study variability , since the region is influenced by the ocean and constant cold fronts that end causing precipitation during most months of the year . This study aims to analyze the variability in rain UGRHI - 2 by analyzing the interference of ENSO events / Southern Oscillation and the Convergence Zone South Atlantic (SACZ) in the amount and distribution of rainfall. The UGRHI helped were created for distribution and control of water in the state of São Paulo , divided watersheds were avoided so that problems such as poor distribution and water shortages in some areas of the state . To study variability , various software , including Excel , Variowin and R statistical package , the subroutine Climatol were used , with the goal of developing isolines showing the spatial distribution of rainfall anomalies in the years studied also the anomaly index was studied rain (IAC) , noting more effectively the years of positive and negative anomaly , with the purpose of studying the temporal variability of rainfall in the study area.